2016
DOI: 10.1001/jamaophthalmol.2016.0316
|View full text |Cite
|
Sign up to set email alerts
|

Supply and Perceived Demand for Teleophthalmology in Triage and Consultations in California Emergency Departments

Abstract: IMPORTANCE Determining the perceived supply and potential demand for teleophthalmology in emergency departments could help mitigate coverage gaps in emergency ophthalmic care. OBJECTIVE To evaluate the perceived current need for and availability of ophthalmologist coverage in California emergency departments and the potential effect of telemedicine for ophthalmology triage and consultation. DESIGN, SETTING, AND PARTICIPANTS Surveys were remotely administered to 187 of the 254 emergency departments throughout C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…These cameras have been proven effective as diagnostic tools for eye diseases including DR, retinopathy of prematurity, age-related macular degeneration, and others. 1 3 , 5 10 Our study demonstrated the effectiveness and practicability of the handheld nonmydriatic fundus camera for examining retinal diseases (Fig. 3 ).…”
Section: Discussionmentioning
confidence: 57%
“…These cameras have been proven effective as diagnostic tools for eye diseases including DR, retinopathy of prematurity, age-related macular degeneration, and others. 1 3 , 5 10 Our study demonstrated the effectiveness and practicability of the handheld nonmydriatic fundus camera for examining retinal diseases (Fig. 3 ).…”
Section: Discussionmentioning
confidence: 57%
“…37 In fact, a recent survey revealed that many ED providers are interested in using teleophthalmology to remotely connect the patient with an ophthalmologist to help triage patients with eye conditions. 38 Direct communication from patients to eye care providers using telemedicine can reduce the number of unnecessary visits to the ED for ocular problems. This trend may already be taking place.…”
Section: Discussionmentioning
confidence: 99%
“…12, 13 Studies have shown that PCPs have low confidence when managing eye complaints. 14, 15 Therefore, patients often receive care from providers who have few resources to determine the presence or urgency of eye disease.…”
mentioning
confidence: 99%